Rozwój regionów dzięki podnoszeniu atrakcyjności produktu narciarskiego - rola organizacji Polskie Stacje Narciarskie i Turystyczne - Jadwiga Berbeka (Ekonomiczne Problemy Turystyki, 2018)
The aim of the article is the discussion of the role of non-government organization: Polish Association of Ski and Tourist Resorts (PASTR) as the platform of ski resorts cooperation in creation, running the business and development. The category: ski product was analyzed from marketing point of view. Factors boosting its attractiveness were pointed out. The estimation of the economic value of Polish ski resorts in the season 2015/2016 was conducted. The value reached 0,49% of Polish GDP. In mezzo scale it is much higher. The contribution of PASTR is crucial